FMRFamid-like neuropeptides as modulators of locomotory reactions in plant parasitic cyst nematodes - T. A. Malyutina; M. V. Voronin (Российский паразитологический журнал, 2022)
The purpose of the research is analysis of world literature dedicated to studies of physiological role and functional importance of FMRFamide-like neuropeptides – components of peptidergic nervous system in cyst nematode plant parasites using an example of 2nd stage larvae of potato and soy nematodes Globodera pallida and Heterodera glycines.The main physiological and functional characteristics of endogenous FMRFamid-like neuropeptides had been found in studies of functional role of flp genes expression of which was discovered in various nerve structures of potato and soy nematodes. The work shows the role of endogenous FMRFamid-like neuropeptides in such plant nematodes' behavior elements as locomotions promoting the parasites' life activity. The functional importance of flp genes coding these biologically active substances and possibilities of using data on physiological effects of neuropeptides on plant nematodes' activity for development of new anthelminthic precise effect drugs are discussed.